Protective effect of Ganoderma lucidum spore extract in trimethylamine‐N‐oxide‐induced cardiac dysfunction in rats. Issue 2 (12th January 2021) - Liu, Yadi; Lai, Guoxiao; Guo, Yinrui; Tang, Xiaocui; Shuai, Ou; Xie, Yizhen; Wu, Qingping; Chen, Diling; Yuan, Xujiang
Abstract: Previous research has shown that the extracts from the Ganoderma lucidum spore (GS) have potentially cardioprotective effects, but there is still abundant room for development in determining its mechanism. In this study, the rat model of cardiac dysfunction was established by intraperitoneal injection of trimethylamine‐ N ‐oxide (TMAO), and the extracts of GS (oil, lipophilic components, and polysaccharides) were given intragastrically at a dose of 50 mg/kg/day to screen the pharmacological active components of GS. After 50 days of treatments, we found that the extraction from GS reduced the levels of total cholesterol, triglyceride, and low‐density lipoprotein; increased the levels of high‐density lipoprotein; and reduced the levels of serum TMAO when compared to the model group ( P < 0.05); especially the GS polysaccharides (DT) and GS lipophilic components (XF) exhibited decreases in serum TMAO compared to TMAO‐induced control. The results of 16S rRNA sequencing showed that GS could change the gut microbiota, increasing the abundance of Firmicutes and Proteobacteria in the DT‐treated group and XF‐treated group, while reducing the abundance of Actinobacteria and Tenericutes . Quantitative proteomics analysis showed that GS extracts (DT and XF) could regulate the expression of some related proteins, such as Ucp1 (XF‐TMAO/M‐TMAO ratio is 2.76), Mpz (8.52), Fasn (2.39), Nefl (1.85), Mtnd5 (0.83), Mtnd2 (0.36), S100a8 (0.69), S100a9 (0.70), and Bdh1 (0.72). The results showed that XF can maintain the metabolic balance and function of the heart by regulating the expression of some proteins related to cardiovascular disease, and DT can reduce the risk of cardiovascular diseases by targeting gut microbiota.